Surface modification of carbon fibre using graphene-related materials for multifunctional composites. - Hung, P. Y.; Lau, K. T.; Fox, B.; Hameed, N.; Lee, J. H.; Hui, D.
Graphene-related materials (GRMs)have been identified as excellent nano-reinforcements for carbon fibre reinforced polymers (CFRPs)with regard to a wide range of engineering applications. GRMs are easily produced from their chief source, graphite, which is relatively affordable and abundantly available around the globe. The outstanding properties of GRMs, such as their large surface area, high mechanical strength and low manufacturing cost bring them to be distinguished nano-reinforcements for CFRPs to form multi-functional and multiscale composites. In this paper, the importance of using GRMs to enhance the properties of CFRPs is highlighted. Different synthesis methods for depositing GRMs onto the surface of carbon fibre and their effectiveness of improving the properties of host materials are reviewed and discussed. At this stage, more works are still needed to understand the basic stress transfer mechanism of GRM-coated CF composites. Their property enhancement at cryogenic environment are crucial for new aircraft and space engineering development.
Keywords: FIBRE/MATRIX BOND; INTERFACE/INTERPHASE; CARBON FIBRE